2022
DOI: 10.3389/fonc.2021.774577
|View full text |Cite
|
Sign up to set email alerts
|

In Real Life, Low-Level HER2 Expression May Be Associated With Better Outcome in HER2-Negative Breast Cancer: A Study of the National Cancer Center, China

Abstract: BackgroundTo characterize the clinical and pathological features and survival of patients with human epidermal growth factor receptor 2 (HER2)-low breast cancer in China.MethodsThe China National Cancer Center database was used to identify 1,433 metastatic breast cancer patients with HER2-negative disease diagnosed between 2005 and 2015. Clinicopathological features, survival, and prognosis information were extracted. Overall survival (OS) was estimated using the Kaplan–Meier method and compared using the log-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 18 publications
9
60
0
Order By: Relevance
“…Nevertheless, there is an ongoing debate on whether HER2-low breast cancer is a distinct entity, but there is a lack of data on this subject, particularly in a Chinese population. A recent published study by our institution analyzed the HER2-low breast cancer in the metastatic setting and concluded that HER2 low expression was related to a better OS ( 21 ). In the present study, we focused on early-stage patients, comparing the clinicopathological characteristics and prognosis between HER2-zero and HER2-low breast cancer with a different HR status.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is an ongoing debate on whether HER2-low breast cancer is a distinct entity, but there is a lack of data on this subject, particularly in a Chinese population. A recent published study by our institution analyzed the HER2-low breast cancer in the metastatic setting and concluded that HER2 low expression was related to a better OS ( 21 ). In the present study, we focused on early-stage patients, comparing the clinicopathological characteristics and prognosis between HER2-zero and HER2-low breast cancer with a different HR status.…”
Section: Discussionmentioning
confidence: 99%
“…In the TNBC population, the frequency of ERBB2 -low expression has been estimated from 21.0% of the patients in our study to 35.0% in previous reports. 14 , 15 We did not notice any difference in tumor grade or the number or type of metastases, whereas de novo metastatic disease was also more frequent in the ERBB2 -low group. Recently, Agostinetto et al 13 presented a retrospective analysis of molecular characteristics of 410 patients with primary ERBB2 -low BC, among whom 74 had TNBC.…”
Section: Discussionmentioning
confidence: 57%
“…All large-scale reports have been based on registry studies that included patients who were treated before the establishment of this new category. Two recently published large studies 15,16 The overall discordance rate from primary tumor to metastasis was 40.9% (1005 tumors).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations